Nutrient Management and Rate of Biostimulant on Hybrid Glutinous Corn - Arevalo, Arnold (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2020)
This study aimed to determine the yield performance of Hybrid glutinous corn in response to nutrient management and rate of biostimulant. It was conducted at Canalum, Nangka, Bayawan City, Negros Oriental from January 2019 to July 2019. The study was laid out using split plot design with three (3) replications. Treatments differences were determined using the Least Significant Different (LSD) test. Results showed that growth and yield parameters differed significantly with independent effects between factors employed. Hybrid glutinous corn applied with different nutrient management differs significantly on parameters used. Treatments applied with 50% organic + 50% in-organic fertilizers got a significant effect on ear height. Meanwhile, treatment with 100% in-organic fertilizer came in next and obtained almost the same or uniformed results with the aforementioned treatment. Finally, treatment applied with 100% organic fertilizer acquired the lowest mean average and always acquired a non-significantly lesser compared from the above mentioned treatments. Hybrid glutinous corn applied with three (3) different levels of megafol differed significantly. At 120ml/16 liters of water of megafol 80ml/16 liters of water of megafol sprayed per hectare there were significant effect on the weight per ear compared to 40ml/16 liters of water of megafol per hectare. All parameters showed that no interaction effect was observed between nutrient management and levels of megafol to the yield performance of hybrid glutinous corn.